Availability and Adequacy of ICT Tools for Teaching Arabic in Colleges of Education, North-central Nigeria - Muhammed, Sanni Abdulhammed (JURNAL IJ-ATL, 2023)
Arabic language is used to access information on the Internet, just like other languages. Its teaching-learning could be enhanced through the use of Information and Communication Technology tools. The inadequate availability as well as the lackadaisical attitude of some teachers to the use of ICT tools in some educational institutions are reported in some works. This study aimed at investigating the level of availability and adequacy of ICT tools for teaching Arabic Language in Colleges of Education in North-central, Nigeria. This study was a descriptive survey research type. The target population and sample consisted of all the 75 lecturers of Arabic in the 15 Colleges of Education in the North-central. The study sample was purposively drawn from the colleges where Arabic was taught. A researcher-developed questionnaire with reliability index of 0.78 was used for data collection. The percentage, One-way Analysis of Variance and the t-test were used for data analysis at 0.05 level of significance. The findings of the study were: out of 23 ICT tools assessed, 14(60.9%) were available  9(39.1%) were not available; 11(47.8%) were adequate 12(52.2%) were not adequate. The study recommended that the government and private proprietors should intervene in the procurement of  unavailable ICT tools.